anonymous
  • anonymous
If f(x) = 3x + 2 and g(x) = 2x – 2, what is (f – g)(x)? x + 4 x – 2 x 5x – 2 x – 4
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Jacob902
  • Jacob902
example If F(x)=3x-2 and g(x)= 2x-1, then g(f(x)) is equal to what?
anonymous
  • anonymous
I need help I don't know how to do this
Jacob902
  • Jacob902
g(f(x)) means that the function g is composed at the function f. You need to plug the value of f(x) into the function g and simplify. g(x) = 2x - 1 Replace x with the value of f(x) which is 3x - 2 and simplify. g(f(x)) = 2x - 1 g(3x - 2) = 2(3x - 2) - 1 g(3x - 2) = 6x - 4 - 1 g(3x - 2) = 6x - 5 So, g(f(x)) = 6x - 5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Jacob902
  • Jacob902
theres an example dont want to give it out
Jacob902
  • Jacob902
without learning
Jacob902
  • Jacob902
nothing
anonymous
  • anonymous
so what is it? can u take me through the steps
Jacob902
  • Jacob902
If f(x)=3x^2+1 and g(x)=2x+2 find a) g^-1(x), the inverse of g(x) b) (fog^-1)(2)
Jacob902
  • Jacob902
If g(x) = 2x + 2, this means it takes an input value, doubles it, and then adds 2. The inverse will do the opposite, in the opposite order. So the inverse will first do the opposite of adding 2, so it subtracts 2, or x - 2. Then it does the opposite of multiplying, by dividing by 2, so (x-2) / 2. So g-1(x)= (x-2) / 2. To find (fog-1)(2), you start by putting 2 into g inverse for x . So g-1(2) = (2-2) /2 , so zero. Then, we put 0 into f, so f(0) = 3(0)2 + 1, so (fog-1)(2) = 1. Hope that helped.
anonymous
  • anonymous
great explanation :)
anonymous
  • anonymous
but what is the answer
anonymous
  • anonymous
\[(f-g)(x)=f(x)-g(x)\] \[\therefore (f-g)(x)=(3x-2)-(2x-2)\] \[=3x-2-2x+2\] \[=3x-2x+2-2\] \[=x+0\] \[\therefore (f-g)(x)=x\]
anonymous
  • anonymous
so it is x=0 right
anonymous
  • anonymous
answer is x
anonymous
  • anonymous
thanks
anonymous
  • anonymous
cheers!
anonymous
  • anonymous
If f(x) = 2x2 + 3x and g(x) = x – 2, what is (f + g)(2)? 16 14 12 10 8
anonymous
  • anonymous
it is 14 right

Looking for something else?

Not the answer you are looking for? Search for more explanations.